The Structure of Indigenous Food Crop Markets in sub-Saharan Africa: The Rice Market in Uganda - Kikuchi, Masao; Haneishi, Yusuke; Tokida, Kunihiro; Maruyama, Atsushi; Asea, Godfrey; Tsuboi, Tatsushi (The Journal of Development Studies, 2016)
Using data obtained from a series of nation-wide market surveys in Uganda, this article attempts to document and assess the domestic rice market at all stages in the post-harvest marketing chain from the farm gate to metropolitan area retail outlets. The criteria used are quantities marketed, prices, marketing margins, marketing costs and net returns to traders. The results show that the regional rice markets are integrated into the national market and that on average little surplus is left for rice traders at all market stages if marketing costs are accounted for. The spontaneously developed indigenous crop market works reasonably well.
Keywords: Indigenous Food Crop Markets; Sub-Saharan Africa; Rice Market; Uganda